Drawing up the protocol in cases of administrative corruption offenses committed in the field of healthcare - B. V. Koval (Bulletin of Kharkiv National University of Internal Affairs)
The scientific article is devoted to the peculiarities of drawing up protocols for administrative corruption offenses committed in health care. The norms of legislation and by-laws have been studied. First of all, the norms of the Code of Administrative Offenses and the Law of Ukraine “On Prevention of Corruption” have been analyzed. The scientists' works devoted to the problems of proceedings in cases of administrative offenses have been studied. Several recommendations have been given to be taken into account by law enforcement officers when drawing up protocols for the commission of a corruption offense in the field of health care. The content features of such protocols have been established. Protocols on the commission of such administrative offenses are most often drawn up by police officers.